Hepatocellular carcinoma in the native liver of a 38-year-old female patient with biliary atresia - Yutaka Kanamori; Masataka Takahashi; Reiko Ito; Katsuhiro Arai; Sachi Koinuma; Yuko Okinaga; Kiyoshi Hasegawa; Norihiro Kokudo (Journal of Pediatric Surgery Case Reports, 2015)
We report a rare case of hepatocellular carcinoma in native liver in a case of biliary atresia. The patient was a 38-year-old female with three children who had an aggressive tumor, resulting in her subsequent death. We also review 14 reports, published previously in the English language medical literature, concerning hepatocellular carcinoma originating from native liver in biliary atresia cases and discuss the possible etiology, and propose more careful follow up for the patients with biliary atresia who suffer from repetitive cholangitis and/or experience the child delivery.